2018
DOI: 10.1371/journal.pone.0193375
|View full text |Cite
|
Sign up to set email alerts
|

Functional and evolutionary implications from the molecular characterization of five spermatophore CHH/MIH/GIH genes in the shrimp Fenneropenaeus merguiensis

Abstract: The recent use of RNA-Seq to study the transcriptomes of different species has helped identify a large number of new genes from different non-model organisms. In this study, five distinctive transcripts encoding for neuropeptide members of the CHH/MIH/GIH family have been identified from the spermatophore transcriptome of the shrimp Fenneropenaeus merguiensis. The size of these transcripts ranged from 531 bp to 1771 bp. Four transcripts encoded different CHH-family subtype I members, and one transcript encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The ORF for the MrGIH cDNA was 360 bp in length and encoded a protein containing 119 amino acids, as also reported in previous studies (Shi et al, 2018;Chen et al, 2020). In addition, multiple sequence alignment and the generation of a phylogenetic tree indicated that MrGIH shared a high degree of similarity to MIH from Macrobrachium nipponense (Qiao et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…The ORF for the MrGIH cDNA was 360 bp in length and encoded a protein containing 119 amino acids, as also reported in previous studies (Shi et al, 2018;Chen et al, 2020). In addition, multiple sequence alignment and the generation of a phylogenetic tree indicated that MrGIH shared a high degree of similarity to MIH from Macrobrachium nipponense (Qiao et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…Besides, type I peptides of the CHH family are also known to suppress ecdysteroidogenesis in the Y-organ, though at a higher dose than MIH 37 . In the L. vannamei genome, we identified three major clades of type I CHH peptides: (1) type Ia CHH clade, which contains peptides more highly expressed in gut, thoracic ganglion and lymphoid organ than in eyestalk and other tissues (Supplementary Data 4), and may function in ion/osmoregulation and water uptake but lack hyperglycemic functions, (2) type Ib clade, which is highly expressed in eyestalk as well as brain and thoracic ganglion, and is less well-studied but also believed to assume an ion/osmoregulatory function 38 , and (3) type Ic clade, which is penaeid-specific and contains peptides involved in the regulation of molting, reproduction, energetics and ionic metabolism 39 (Fig. 4e).…”
Section: Resultsmentioning
confidence: 99%
“…These are “paraneurones” which secrete CHH into the hemolymph during ecdysis ( 68 , 124 ). Since then, it has been shown that CHH-related peptides are expressed in a wide variety of tissues including the pericardial organ ( 120 , 125 ), retina ( 126 ), gill ( 60 , 127 ), spermatophore ( 71 , 128 ), Y-organ ( 121 , 129 ), hemocyte ( 70 , 72 ), ovary ( 129 , 130 ), stomach ( 130 ), and intestine ( 54 ).…”
Section: Evolution and Structural Diversification Of The Superfamilymentioning
confidence: 99%
“…While the XO-SG complex in the eyestalk is the first tissue from which the crustacean members of the CHH superfamily were isolated and most likely the main source of these peptides, it has been shown that they are also expressed in other nervous and non-nervous tissues [e.g., (47,48,50,53,55,(67)(68)(69)(70)(71)(72)]. Similarly, ITP and ITP-L are widely expressed in the central and peripheral nervous system (49,73,74).…”
Section: Introductionmentioning
confidence: 99%